Efektivitas Penyaluran Bantuan Langsung Tunai Kepada Masyarakat Miskin di Masa Pandemi Covid-19 - Fivin Sri Widyastui; Patta Hindi Asis; La Ode Abdul Harlan (Parabela: Jurnal Ilmu Pemerintahan & Politik Lokal, 2022)
The problem in this study is how effective cash direct assistance (Bantuan Langsung Tunai, BLT) is in improving the welfare of the poor during the COVID-19 pandemic, while the goal to be achieved in this study is to determine the effectiveness of direct cash assistance (BLT) in improving the welfare of the poor in during the COVID-19 pandemic in Sikeli Village, West Kabaena District, Bombana Regency. In this study, we used a qualitative descriptive to analysis techniques by collecting data with conducting observations, interviews and documentation. The data obtained presented in the form of explanations, descriptions and describing the actual reality so that it becomes clear about the effectiveness of BLT in improving the welfare of the poor during the COVID-19 pandemic in Sikeli Village, West Kabaena District, Bombana Regency. The results of this study indicate that the effectiveness of Direct Cash Assistance (BLT) in Sikeli Village in improving the welfare of the poor has not been effective even though it has been carried out according to procedures but in the process of determining prospective BLT recipients there are still indications of nepotism carried out by government elements in Sikeli Village, in Judging from the accuracy of the targeting of BLT recipients, the Government has indeed worked optimally and complied with existing procedures, even though the beneficiaries of the BLT program are still not fully targeted. Besides that, basically BLT is expected to help the government in overcoming poverty and maintaining the consumption level of Target Households due to the COVID-19 pandemic, on the other hand the BLT program is a short-term program that is temporary. The program is only running certain circumstances, which is when the world economic crisis occurs which has an impact on the national economy.